2018
DOI: 10.1002/stc.2254
|View full text |Cite
|
Sign up to set email alerts
|

Serviceability assessment for long-span suspension bridge based on deflection measurements

Abstract: Summary Serviceability issues related to service load deformations is of great importance to in‐service bridge maintenance decision making. Development in structural health monitoring brings opportunities to serviceability assessment for long‐span bridges. In this study, a reliability assessment framework of traffic‐induced vertical deflection is developed by incorporating extreme values analysis and system reliability with deflection measurements. The framework includes the following steps: (a) identifying tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…where c is the cohesion of surrounding rock, φ is the internal friction angle of surrounding rock, and A′ is the effective contact area of the bottom sliding surface. e other parameters are the same as (6). e Poisson effect of the plug body and the effect of surrounding rock pressure on the interface are considered in formula (5).…”
Section: Calculation Methods Of Upliftmentioning
confidence: 99%
See 1 more Smart Citation
“…where c is the cohesion of surrounding rock, φ is the internal friction angle of surrounding rock, and A′ is the effective contact area of the bottom sliding surface. e other parameters are the same as (6). e Poisson effect of the plug body and the effect of surrounding rock pressure on the interface are considered in formula (5).…”
Section: Calculation Methods Of Upliftmentioning
confidence: 99%
“…Cable-supported bridges come in cable-stayed and suspension forms; one of the main forms of long-span bridges are suspension bridges [3,4], which are one of the main models [5], because it has significant advantages in exerting material properties and height-span ratio of stiffening girder. Being flexible, suspension bridges are mainly composed of main beam, tower pier, cable, and anchorage, in which anchorage is the key structure of anchoring main cable of suspension bridge [6] (Figure 1). Suspension bridge can be classified as self-anchored suspension and groundanchored suspension [7].…”
Section: Introductionmentioning
confidence: 99%
“…The deflections of the span show directly the stress of the bridge construction caused by the external loads action, and therefore, by measuring their values, it is possible to get a more accurate estimation of a structure state 2 . In engineering practice, triangulation, hydrostatic leveling, 15 fiber optic, or LVDT sensors 3 are used to measure displacements.…”
Section: Technique For Measuring the Bridge Span Elements Movementmentioning
confidence: 99%
“…Bridges state estimation takes into consideration peculiarities of their construction, age and external natural factors, working conditions, traffic intensity as well as measurement experimental data of bridge construction elements deformation, inclination, and displacement caused by working load. In order to ensure modern requirements for bridges reliable exploitation, regular monitoring of construction state should be provided by using various instrumental methods 1–16 . During monitoring the structural health, any anomalies can be detected in time.…”
Section: Introductionmentioning
confidence: 99%
“…For CPS, the changes of liquid levels in the connected pipes detected by pressure transmitters are used as the indicators, which can reflect the deflection changes of bridge. Deng et al [ 12 ] utilized this method to monitor a long-span suspension bridge and assessed the serviceability reliability of vertical deflections. The results demonstrated that the CPS presented an excellent capacity to track the deflection under actual traffic conditions.…”
Section: Introductionmentioning
confidence: 99%